FERRIC CITRATE: AN IRON-BASED ORAL PHOSPHATE BINDER - T. Christopher Bond; Rich Mutell; Stephen Wang; Enrique Poradosu; Robert Niecestro Tracy (The Korean Society of Nephrology, 2012)
Patients with end-stage renal disease (ESRD) often experience secondary bone and mineral disorder requiring treatment with phosphate-binder (PB) medications, vitamin D sterols, and calcimimetics. Ferric citrate is an oral, iron-based PB in clinical development that has been shown to reduce serum phosphorus while increasing serum ferritin and transferrin saturation (TSAT) in ESRD patients. In a Phase 2 study, patients receiving ferric citrate experienced significant increases in serum ferritin (+10%) and TSAT (+18%) after 4 weeks of treatment. We analyzed electronic medical records of patients with concurrent rises in TSAT (≥ 10%) and ferritin (15% to 25%) between 6/1/08 and 12/31/10, excluding patients with significant change in iron or erythropoiesis-stimulating agent (ESA) dose, hemoglobin, or change in PB during the prior month. We assessed changes in epoetin alfa and iron dosing when physicians observed these increases in lab values. We constructed a cost offset model from a per patient per month (PPPM) considering average sales price of epoetin and iron that assumed equivalent phosphorus outcomes and pricing across all PB. The analysis included 2,037 concurrent, non-treatment related rises in ferritin and TSAT. Decreases in dose/dialysis session in mean epoetin and iron use 2 months following the index date represented an average combined savings of $90.51 to $181.01 PPPM. The model was most sensitive to baseline drug doses: patients at highest baseline epoetin doses (> 9,000U/session) showed savings of $471.80 to $943.61 PPPM. Based on actual physician behavior in response to ferritin and TSAT increases and ferric citrate clinical trial results, and assuming equivalent pricing to other PBs, there would be cost savings with ferric citrate use through reduced ESA and iron use.